Análise de eficientização energética de uma indústria cerâmica - VILA SÊCA, Marcelo Paixão (2018)
The most used form of energy is electrical, and reducing its use became a point of concern for consumer groups, particularly for the industrial sector due to their high consumption of electricity. This concern made possible for industrial projects focused on efficiency of processes to receive more attention every day, due to its importance in reducing energy consumption, in addition to the outcomes which provide reduced environmental impacts, increased competitiveness in the economy and especially in the search to secure energy supply. Thus, this work presents a case of study of analysis and power efficiency in the Corte Real Ceramic, located in Tucuruí - PA. In such case, analysis of electrical character on the engine and lighting systems were performed through the use of software, such as BDMOTOR and DIALUX EVO, as well as studies on the contract for power supply, firmed by the company under investigation with the local utility, following the methodology and recommendations provided by PROCEL. Thereby, based on the results obtained from the developed studies it is expected to achieve a reduction in the use of electricity aligned with rationalization of consumption by determining inefficient processes and offering optimization proposals.